INTEGRATION OF DEEP LEARNING AS AN EDUCATIONAL INNOVATION STRATEGY FOR ISLAMIC BOARDING SCHOOLS (PESANTREN) IN THE DIGITAL ERA - Muzakir, Muchammad Ibnu; Akhirudin, Muhammad Towil; Idham, Idham; Samiyono, Samiyono (Asosiasi Dosen Perguruan Tinggi Islam, 2025)
This study explores the integration of the pedagogical Deep Learning (DL) approach, specifically the Meaningful, Mindful, and Joyful (MMJ) framework, within the traditional educational system of Indonesian pesantren. The aim is to analyze the compatibility, challenges, and operationalization of DL to enhance learning outcomes and prepare students for the demands of the digital era. A qualitative case study approach was employed at pesantren Darunnajah in Bogor, involving in-depth interviews with 12 participants (3 teachers, 6 students, and 3 administrators), observations, and document analysis. The findings highlight a strong theoretical alignment between DL and pesantren's core educational values, such as Fahm (deep comprehension), Ijtihad (critical reasoning), and Adab (moral development). Empirically, teachers reported improved student engagement and reflective learning practices, with one educator noting,